The Long-Run Effects of Reducing Early School Tracking - Serena Canaan (Institute of Labor Economics (IZA), 2019)
Grouping students by ability is a controversial issue, and its impacts are likely to depend on the type of tracking students are exposed to. This paper studies a reform that moved French schools from a rigorous tracking system, which assigned students to tracks with significantly different learning environments and career options, to a milder form of ability-tracking that only grouped students into different classrooms. Using a regression discontinuity design, I find that the reform raised individuals' level of education and increased their wages by 4.7 percent at ages 40 to 45, with the strongest effects occurring among individuals from low socioeconomic backgrounds.
Keywords: I21; I28; J24; 330; tracking; returns to education; school quality